Faktor - Faktor Yang Berhubungan Dengan Penggunaan Wadah Styrofoam Sebagai Wadah Makanan Pada Penjual Jajanan Di Jalan William Iskandar Kecamatan Medan Tembung - Muhammad Crystandy; Neni Ekowati Januariana; Aldilla Rahmadhani (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Styrofoam is a material made of polytrene packaging which is generally white and rigid which is often used as food packaging boxes. Previously, this material was used to protect non-food items such as electronic items to withstand light impacts, but nowadays it is often used as a packaging box. The purpose of this study was to determine the factors associated with the use of Styrofoam containers as food containers for street food vendors on Jalan William Iskandar, Medan Tembung District. The research design is an analytic survey with a cross sectional design. The population of this study were all food sellers along Jalan Iskandar William, namely 93 respondents who were also used as samples for the analysis research used univariate and bivariate. The results of the study showed that all educational variables were p = 0.005, knowledge p = 0.002, attitude p = 0.000, meaning that there was a relationship with the use of styrofoam containers as food containers for snack vendors. The conclusion of this study all variables related to the use of styrofoam containers as food containers at street vendors on William Iskandar Street, Medan Tembung District. It is recommended to street food vendors to reduce the use of Styrofoam containers as food containers that have a negative impact on health and the environment if used continuously.Keywords: Education, Knowledge, Attitude, Use of Styrofoam Containers